Long‐term adherence and response to botulinum toxin in different indications. Issue 1 (1st December 2020) - Lee, John‐Ih; Jansen, Alexander; Samadzadeh, Sara; Kahlen, Ulrike; Moll, Marek; Ringelstein, Marius; Soncin, Giulia; Bigalke, Hans; Aktas, Orhan; Moldovan, Alexia‐Sabine; Waskoenig, Julia; Jander, Sebastian; et al.
Abstract: Objective: The objective of the study was the analysis of adherence and self‐perceived treatment response to long‐term botulinum neurotoxin type A (BoNT‐A) treatment in different neurological indications. Methods: In this retrospective, monocentric, observational study, cross‐sectional and longitudinal data of 1351 patients documenting 20705 injection appointments at the BoNT outpatient clinic of Heinrich Heine University Duesseldorf between 1989 and 2014 were retrospectively analyzed. Patients had been treated with BoNT for neurological conditions, including cervical dystonia (CD), blepharospasm (BSP), other dystonia (ODT), hemifacial spasm (HFS), and spasticity (SPAS). The parameters longitudinally analyzed for the entire cohort were therapy duration as well as the mean and cumulative BoNT‐A dose. Cross‐sectionally, for subgroups of at least 721, patients' global self‐perceived quality of health and life, global self‐perceived reduction of symptoms by BoNT‐A treatment as well as the clinical global impression were evaluated. Furthermore, mouse hemidiaphragm assay antibodies (MHDA‐ABs) were analyzed in a subgroup. Results: The mean treatment duration was 4.58 years (95% CI 4.32–4.84), and 678 (50.2%) therapy dropouts of 1351 patients occurred within the first 8 years. Therapy adherence and self‐perceived symptom reduction in long‐term BoNT‐A treatment over the years were significantly longer in BSP, HFS, and CD patients than in ODT and SPAS patients. Interpretation: The treatment indication determines long‐term adherence and self‐perceived symptom reduction in BoNT‐A therapy, which are better in BSP, HFS, and CD patients than in ODT and SPAS patients. MHDA‐ABs had a significant impact on global self‐perceived symptom reduction, but with only a limited degree.